Case Report: Combination of Pressure Guidewire and Optical Coherence Tomography-Guided Drug-Coated Balloon Revascularization for Renal Artery Fibromuscular Dysplasia - Li, Yuxi; Wen, Xinyan; Zheng, Bo; Chen, Ming; Ma, Wei; Li, Jianping (Frontiers in Cardiovascular Medicine, 2022)
Fibromuscular dysplasia (FMD) is the second common cause of renovascular hypertension. With the advent of endovascular therapy, angiography has become a diagnostic gold standard for FMD. Optical coherence tomography (OCT) by reflecting in vivo histology may improve the diagnostic and classification accuracy. Renal fractional flow reserve (rFFR), measured by pressure guidewire, may distinguish the patients who may benefit from revascularization by identifying physiologically significant stenoses. However, the role of usage of both OCT and rFFR is not well studied. We herein report a 17-year-old male with renovascular hypertension due to FMD. Angioplasty of drug coated balloon (DCB) guided by OCT and FFR favorably achieved blood pressure control. In conclusion, the utility of both OCT and FFR may be useful for appropriate selection of patients with renal FMD.